Electrophysiologic research of surgically restored median nerve (experimental study). - Borzykh, N. O.; Strafun, S. S.; Savosko, S. I. (Medicni Perspektivi, 2018)
In the experiment the possibility of providing effective regeneration of the injured median nerve in conditions of creation “protected” suture with intact ulnar nerve was studied. Experimental animals were divided into 4 groups: 1) complete neurotomy of the median nerve; 2) complete neurotomy of the median nerve with neurorrhaphy; 3) complete neurotomy of the median nerve and anastomosis creation between the median and the ulnar nerves in the distal site; 4) complete neurotomy of the median nerve and its neurorrhaphy with the anastomosis between the median and the ulnar nerves in the distal site. The histological study was carried out to identify the level of the nerve regeneration, state of the nerve distal segment and electrical conductivity of the surgically restored nerve on day 30 after the trauma. Morphometric and electrophysiological examinations showed that anastomosis creation allows to prevent atrophy and elimination of distal segment of median nerve and activate regenerative process in the injured nerve. The electrical conductivity of the nerve improved. An increased M-response of the forearm muscles was observed in groups with the anastomosis between the median and the ulnar nerves (the level of M-response recovery in the group 2 – 27,1%, group 3 – 18, 9%, group 4 – 84,6%). According to the study results we have made a conclusion that reinnervation of the muscles at an early stage of the median and the ulnar nerves regeneration was realized with the participation of high-threshold myelin nerve fibers.